Metal to phosphorus stoichiometries for freshwater phytoplankton in three Scottish lakes - Gormley-Gallagher, Aine M; Douglas, Richard; Rippey, Brian (PeerJ PrePrints, 2014)
Simultaneous measurements of changes in phytoplankton biomass and the metal and phosphorus (P) content of cells have been captured to attest metal to P stoichiometries for freshwater phytoplankton. Three remote Scottish lakes that have received high, medium or low metal contamination from the atmosphere were selected for study. Phytoplankton cells were collected, their biomass determined microscopically, and Inductively Coupled Plasma-Mass Spectrometry was used to measure their lead (Pb), cadmium (Cd), mercury (Hg), copper (Cu), zinc (Zn), nickel (Ni), chromium (Cr), manganese (Mn), cobalt (Co) and P content. A greater phytoplankton biomass in the lakes resulted in significant algae growth dilution of the mass-specific Pb, Cd, Hg, Cu, Ni and Cr in the phytoplankton. Changes in the phytoplankton cell count and their Hg, Pb, Cd, Cu, Mn, Co, Ni and Cr concentrations showed the process of algae bloom dilution to be subject to exponential decay, which accelerated in the order of Mn < Cu < Ni < Pb and Cd < Cr and Hg < Co. This indicated a metabolic and detoxification mechanism was involved in the active selection of metals. For the first time simultaneous measurements of metals and P stoichiometry in freshwater phytoplankton are reported. The mean metal to P stoichiometry generated was (C106P1N16)1000Pb0.019Hg0.00004Cu0.013Cd0.005Cr0.2Co0.0008 Mn0.2Ni0.012 based on the field measurements and the Redfield average C, N and P stoichiometry of (CH2O)106(NH3)16H3PO4.
Keywords: metal; phytoplankton; phosphorus; freshwater; lakes; stoichiometries; scotland